2005
DOI: 10.1073/pnas.0508377102
|View full text |Cite
|
Sign up to set email alerts
|

Dental senescence in a long-lived primate links infant survival to rainfall

Abstract: Primates tend to be long-lived, and, except for humans, most primate females are able to reproduce into old age. Although aging in most mammals is accompanied by dental senescence due to advanced wear, primates have low-crowned teeth that wear down before old age. Because tooth wear alters crown features gradually, testing whether early dental senescence causes reproductive senescence has been difficult. To identify whether and when low-crowned teeth compromise reproductive success, we used a 20-year field stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

8
268
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 206 publications
(277 citation statements)
references
References 36 publications
(52 reference statements)
8
268
0
Order By: Relevance
“…Population growth rates of the closely related Verreaux's sifaka (Propithecus verrauxi), inhabiting southern dry forests, have been found to be most sensitive to drought conditions (Lawler et al, 2009). In RNP, King et al (2005) demonstrated that aging P. edwardsi females with senescent teeth had little success raising young especially in years with dry lactation seasons. Drought during lactation in the present study was negatively associated with first year survival but with relatively low weighted importance (Table 2), and was not associated with fecundity overall, suggesting that at current levels, it is unlikely to have much effect on population dynamics.…”
Section: Climate and Demographymentioning
confidence: 99%
See 2 more Smart Citations
“…Population growth rates of the closely related Verreaux's sifaka (Propithecus verrauxi), inhabiting southern dry forests, have been found to be most sensitive to drought conditions (Lawler et al, 2009). In RNP, King et al (2005) demonstrated that aging P. edwardsi females with senescent teeth had little success raising young especially in years with dry lactation seasons. Drought during lactation in the present study was negatively associated with first year survival but with relatively low weighted importance (Table 2), and was not associated with fecundity overall, suggesting that at current levels, it is unlikely to have much effect on population dynamics.…”
Section: Climate and Demographymentioning
confidence: 99%
“…We had expected that drought would be one of the most important factors likely to threaten P. edwardsi populations in the face of climate variability (Wright, 2006;Dunham et al, 2008) based on suggestions of prior studies (Gould et al, 1999;Richard et al, 2000;King et al, 2005). Population growth rates of the closely related Verreaux's sifaka (Propithecus verrauxi), inhabiting southern dry forests, have been found to be most sensitive to drought conditions (Lawler et al, 2009).…”
Section: Climate and Demographymentioning
confidence: 99%
See 1 more Smart Citation
“…Although this result may at first seem counterintuitive, King et al (1) point out that fertility is not necessarily the best measure of reproductive success. In this case, mortality rates are higher for infants of dentally senescent mothers.…”
mentioning
confidence: 83%
“…A similar study of stomach contents in Milne Edwards' sifakas, along with analyses of milk production and nutrient content, would go a long way toward confirming links between dental morphology, lactation, and environment. Nevertheless, by combining long-term field studies with dental topographic analyses, King et al (1) offer an exciting new way of thinking about occlusal morphology, reproductive fitness, and natural selection. This research challenges the rest of us, raising the bar not only on analyses of tooth wear but also on all studies of adaptive form and function.…”
mentioning
confidence: 99%